Monoclonal antibodies for characterization of rabies virus isolated from non-hematophagous bats in Brazil - Luciana Botelho Chaves; Samira Maria Achkar; Andréa de Cássia Rodrigues da Silva; Graciane Maria Medeiros Caporale; Paula Sônia Cruz; Alexandre Mendes Batista; Karin Corrêa Scheffer; Irene Fernades; Maria Luiza Carrieri; Elizabeth N De Gaspari (Journal of Infection in Developing Countries)
Introduction: In Brazil, various isolates of rabies virus (RABV) show antigenic profiles distinct from those established by the reduced panel of eight monoclonal antibodies (MAbs) determined by the Centers for Disease Control and Prevention (CDC), utilized for the antigenic characterization of RABV in the Americas. The objective of this study was to produce MAbs from RABV isolates from insectivorous bats with an antigenic profile incompatible with the pre-established one. Methodology: An isolate of RABV from the species Eptesicus furinalis that showed an antigenic profile incompatible with the panel utilized was selected. Hybridomas were produced utilizing the popliteal lymph nodes of mice immunized with ribonucleoproteins purified from the isolate. Results: Two MAbs-producing clones were obtained, BR/IP1-3A7 and BR/IP2-4E10. Fifty-seven isolates of RABV from different species of animals and different regions of Brazil were analyzed utilizing the MAbs obtained. In the analysis of 23 RABV isolates from non-hematophagous bats, the MAbs cross-reacted with ten isolates, of which four were of the species Nyctinomops laticaudatus, one of the species Eptesicus furinalis, and five of the genus Artibeus. Of the nine isolates of non-hematophagous isolates that displayed an incompatible profile analyzed, characteristic of insectivorous bats, BR/IP1-3A7 reacted with five (55.55%) and BR/IP2-4E10 with four (44.44%). Conclusions: The MAbs obtained were able to recognize epitopes common between the three genera, Artibeus, Eptesicus, and Nyctinomops, thereby allowing the antigenic characterization of RABV isolates in Brazil.